How to regulate faith schools. (9th October 2018) - Clayton, Matthew; Mason, Andrew; Swift, Adam; Wareham, Ruth
Abstract: Should the state collaborate with religious organisations in the provision of schooling – and if it does, how much room is there for compromise on curriculum, pedagogy, staffing and admissions? How should the regulation of state‐maintained faith schools differ from the regulation of other state‐maintained schools? How, if at all, should the state regulate faith‐based education in the independent sector and in the home? In this groundbreaking pamphlet, Matthew Clayton, Andrew Mason, Adam Swift and Ruth Wareham tackle these questions head on. They advocate an outright ban on (confessional) religious instruction in state‐funded schools, along with a universal entitlement to an adequate programme of civic, religious, ethical and moral education. They argue that it is acceptable for schools to have a 'faith ethos', and to select up to 50% of pupils on the basis of faith, as long as steps are taken to safeguard the development of children's autonomy. And they propose that faith schools in the independent sector should only retain their charitable status if they submit to the same regulation as those in receipt of state funding. How to regulate faith schools is a bold, compelling and timely intervention in the public debate about faith‐based education in the UK. The author's policy recommendations are coherent, cogent and sensitive to the real‐world constraints under which education policy is made. The result is a powerful regulatory framework that is both rigorously justified and practically feasible.